Respostas
respondido por:
21
√8 · √6 = √48
√21 · √7 = √147
Portanto:
√8 · √6 + √21 · √7 = √48 + √147
Mas √147 = 3·7·7 = 3 ·7²
√48 = 2·2·2·2·3 = 3·2²·2²
√48 + √147 = √(3·2²·2²) + √(3 ·7²)
= 2·2·√3 + 7·√3
=4·√3 + 7·√3
= 11√3
√21 · √7 = √147
Portanto:
√8 · √6 + √21 · √7 = √48 + √147
Mas √147 = 3·7·7 = 3 ·7²
√48 = 2·2·2·2·3 = 3·2²·2²
√48 + √147 = √(3·2²·2²) + √(3 ·7²)
= 2·2·√3 + 7·√3
=4·√3 + 7·√3
= 11√3
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás